2021
DOI: 10.3390/antiox10111814
|View full text |Cite
|
Sign up to set email alerts
|

Plant Extract of Limonium gmelinii Attenuates Oxidative Responses in Neurons, Astrocytes, and Cerebral Endothelial Cells In Vitro and Improves Motor Functions of Rats after Middle Cerebral Artery Occlusion

Abstract: There are numerous publications demonstrating that plant polyphenols can reduce oxidative stress and inflammatory processes in the brain. In the present study we have investigated the neuroprotective effect of plant extract isolated from the roots of L. gmelinii since it contains a rich source of polyphenols and other biologically active compounds. We have applied an oxidative and inflammatory model induced by NMDA, H2O2, and TNF-α in human primary neurons and astrocytes, and mouse cerebral endothelial cell (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…We have compiled these relationships into a novel astrocyte-centric model for DMD and AD ( Fig. 6 ) [ [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] ], which may further pave the way toward novel therapeutic approaches targeting reactive astrocytes [ 74 ] to overcome the cognitive dysfunction associated with DMD.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…We have compiled these relationships into a novel astrocyte-centric model for DMD and AD ( Fig. 6 ) [ [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] ], which may further pave the way toward novel therapeutic approaches targeting reactive astrocytes [ 74 ] to overcome the cognitive dysfunction associated with DMD.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…The Limonium root extracts had found as active inhibitors of key enzymes such as, acetylcholinesterase, butyrylcholinesterase, amylase, tyrosinase and glucosidase, which are play roles in various diseases [20]. In addition, L. gmelinii root extract had protective responded to oxidative stress in brain and can improve motor functions both in vitro and in vivo model [21]. Hence, we are suggested that further studies will be conduct on evaluation of key enzyme inhibition by S. maritima root and its bioactive compound characterizations.…”
Section: Discussionmentioning
confidence: 99%
“…As such, preclinical tests of an extract from L. gmelinii roots showed its antioxidant, hepatoprotective, antibacterial, antimutagenic, antitumor, and antiviral properties [16,17]. It has also been shown that extracts from the roots and rhizomes of L. gmelinii protect neurons, astrocytes, and cerebral endothelial cells from oxidative and inflammatory responses in vitro and improve motor functions after ischemic stroke in vivo [18]. Data on the antidiabetic, cytotoxic, and anti-inflammatory properties of lignanamides isolated from the ethyl acetate extract of L. gmelinii roots [19].…”
Section: Introductionmentioning
confidence: 98%
“…Flavonoids were one of the major classes of compounds observed in the extracts. The tentative characterization of flavonoids was performed on the basis of our previous in-house report [18]. Gallocatechin, apigenin, quercetin, and myricetin derivatives, as well as their aglycone fragment ions, were the main flavonoids, as shown in Table 2.…”
mentioning
confidence: 99%